Possibilities of Long-Range Forecast of Weather Conditions over the Antarctic Peninsula - Martazinova, V.F.; Maderich, V.S.; Tymofeyev, V.Y.; Ivanova, E.K. (Український антарктичний журнал, 2009)
Developed by us in 1998 the method of long-range weather forecast for the moderate latitudes of Northern hemisphere is based on two-month similarity of atmospheric circulation which is well revealed by the traditional method of analogues of one season. That is why similarity of atmospheric processes in the non-tropical latitudes of Southern hemisphere was also explored by the method of traditional analogue. Similarity between the processes of successive days on the fixed territory taking into account the coincidence of all geographical coordinates allowed to set in Southern hemisphere two-month quasi-periodicity of large-scale and consequently regional atmospheric circulation.